(untitled) (Construction Economics and Building, 2013)
Though extant literatures in other sectors indicate that job satisfaction and organizational commitment are important for determining individual and organisational outcomes, limited related research has been conducted amongst quantity surveyors in Hong Kong. Given cooperative working arrangement in the quantity surveying profession, work group identification is regarded as an important antecedent for determining job satisfaction and organisational commitment. The aim of this study is to examine whether work group identification improves job satisfaction and organisational commitment. A questionnaire survey is conducted to collect data from quantity surveyors working in private sector. A total of 71 valid responses are obtained from 509 contacted quantity surveyors in Hong Kong. Bivariate correlation and multiple regression analyses are performed to find the significance of relationships among the variables. Data analysis results support most hypotheses. Work group identification is found to have significant positive effect on job satisfaction, affective and normative commitment. The finding is a bold step for quantity surveying companies to improve their quantity surveyors’job satisfaction and commitment level. The role of other contextual and organisational factors on job satisfaction and organisational commitment needs to be complemented for future research.